2017
DOI: 10.1007/s00431-017-2968-y
|View full text |Cite
|
Sign up to set email alerts
|

Early hypovolemic shock and abdominal distention due to neonatal splenic rupture: urgency of diagnosis and management

Abstract: This pathology must be known to the neonatologist so that she/he can quickly evoke it, given that it can quickly become life-threatening. What is known: • Splenic rupture in the neonatal period is a rare condition that can be complicated by hemorrhagic shock and quickly lead to the death of the newborn. • The symptoms are not very specific, rendering the diagnosis difficult and often delayed. What is new: • This is the first publication bringing together as many clinical cases on the subject reporting in parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 12 publications
0
10
0
1
Order By: Relevance
“…Splenic rupture and splenic hemorrhage occur in two stages. The first stage is subcapsular hematoma formation, which is often asymptomatic, whereas the second stage is capsular rupture which leads to the development of acute symptoms of decompensation and the rapid onset of hypovolemic shock (30). The present study revealed that early presentation at ≤12 h of age was associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Splenic rupture and splenic hemorrhage occur in two stages. The first stage is subcapsular hematoma formation, which is often asymptomatic, whereas the second stage is capsular rupture which leads to the development of acute symptoms of decompensation and the rapid onset of hypovolemic shock (30). The present study revealed that early presentation at ≤12 h of age was associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 58%
“…Clinicians should suspect abdominal hemorrhage if patients had unexplained anemia. Hepatic lesions (65%) account for the most frequent causes of intra-abdominal hemorrhage, followed by adrenal lesions (15%) and splenic lesion (10%) (30). Hepatic laceration should be considered if the patient underwent umbilical venous catheter insertion (32).…”
Section: Discussionmentioning
confidence: 99%
“…Hemoperitoneum secondary to splenic rupture is most often due to stretching of the splenorenal ligament and is usually associated with dystocia and difficulties of extraction. 3 The mechanism involved could be an elevated fetal intrathoracic pressure during uterine contractions, which pushes the liver and spleen out of the diaphragmatic cavity, resulting in an excessive strain to their supporting ligaments. 4 In this case, the mother had experienced the delivery as traumatic.…”
Section: Discussionmentioning
confidence: 99%
“…4 Of note, a recently published article describes 5 cases of infants with splenic rupture who were critically ill at birth and had signs of fetal distress prior to delivery, perhaps describing an alternative mechanism of splenic injury than those reviewed in this article. 5…”
Section: Discussionmentioning
confidence: 99%
“…4 Of note, a recently published article describes 5 cases of infants with splenic rupture who were critically ill at birth and had signs of fetal distress prior to delivery, perhaps describing an alternative mechanism of splenic injury than those reviewed in this article. 5 The underlying cause for the bleeding is highly variable. One case describes maternal trauma prior to delivery as the possible cause for splenic damage, 6 but most cases assume the delivery itself was the inciting event, especially in the case of a traumatic or difficult delivery, 2,7-9 an intrinsic bleeding disorder such as hemophilia A [10][11][12] or other clinical entities such as a wandering spleen, 13 splenic hemangioendothelioma, 14 and splenomegaly caused by erythroblastosis fetalis.…”
Section: Discussionmentioning
confidence: 99%